THE COMPLEXITY OF THE CONCEPT OF ISLAMIC REVIVALISM AND REVIVALISTS’ UNDERSTANDING OF A PROPER MODEL OF STATE - IŠKAUSKAITĖ, RAIMONDA (Politologija, 2012)
Islamic Revivalism is not a brand-new phenomenon, but, with increasing files of exponents, it promotes a variety of discussions on how and when it started, what is the mainstream ideology, what are the foremost goals of its activists, etc. Summing up all the analysis and propositions, it could be stated that the phenomenon of Islamic Revivalism (which started, the latest, with the Iranian revolution) designates all-out efforts aimed at the wholesale re-islamization of polities through direct political and/or military actions. As the definition suggests, the goal of revivalists (a proper Islamic state with three key elements: Islam, Sharia, Islamic ruling system) is the same but the approach to reaching it might not be indiscrete. Therefore, Sunni Islamic revivalists, who are the main object of the research, are divided into three groups: islamists (the most moderate Muslim revivalists with political goals), fundamentalists (who might radically impose religion on politics, though do not necessarily will claim to have a political project), and radical Muslims (who are committed to violence and seek for their goals on any terms).